Surface Enhancement Using Black Coatings for Sensor Applications - Hruška, Martin; More-Chevalier, Joris; Fitl, Přemysl; Novotný, Michal; Hruška, Petr; Prokop, Dejan; Pokorný, Petr; Kejzlar, Jan; Gadenne, Virginie; Patrone, Lionel; Vrňata, Martin; Lančok, Jan (Nanomaterials (Basel, Switzerland), 2022)
The resolution of a quartz crystal microbalance (QCM) is particularly crucial for gas sensor applications where low concentrations are detected. This resolution can be improved by increasing the effective surface of QCM electrodes and, thereby, enhancing their sensitivity. For this purpose, various researchers have investigated the use of micro-structured materials with promising results. Herein, we propose the use of easy-to-manufacture metal blacks that are highly structured even on a nanoscale level and thus provide more bonding sites for gas analytes. Two different black metals with thicknesses of 280 nm, black aluminum (B-Al) and black gold (B-Au), were deposited onto the sensor surface to improve the sensitivity following the Sauerbrey equation. Both layers present a high surface roughness due to their cauliflower morphology structure. A high response (i.e., resonant frequency shift) of these QCM sensors coated with a black metal layer was obtained. Two gaseous analytes, H2O vapor and EtOH vapor, at different concentrations, are tested, and a distinct improvement of sensitivity is observed for the QCM sensors coated with a black metal layer compared to the blank ones, without strong side effects on resonance frequency stability or mechanical quality factor. An approximately 10 times higher sensitivity to EtOH gas is reported for the QCM coated with a black gold layer compared to the blank QCM sensor.
Keywords: sensor applications; black gold; QCM sensors; black aluminium; evaporation depositions; sputtering depositions; nanostructured materials